Electrocatalytically inactive SnS2 promotes water adsorption/dissociation on molybdenum dichalcogenides for accelerated alkaline hydrogen evolution. (October 2019) - Chen, Yaping; Wang, Xingyong; Lao, Mengmeng; Rui, Kun; Zheng, Xiaobo; Yu, Haibo; Ma, Jing; Dou, Shi Xue; Sun, Wenping
Abstract: Molybdenum dichalcogenides, in particular, MoS2 and MoSe2, are very promising nonprecious metal-based electrocatalysts for hydrogen evolution reaction (HER) in acidic media. They exhibit inferior alkaline HER activity, however, due to the sluggish water dissociation process. Here, we design and synthesize new molybdenum dichalcogenide-based heterostructures with the basal planes decorated with SnS2 quantum dots towards enhanced alkaline HER activity. The electrochemical results reveal that the alkaline hydrogen evolution kinetics of molybdenum dichalcogenides is substantially accelerated after incorporation of SnS2 quantum dots. The optimal MoSe2 /SnS2 heterostructure delivers a much lower overpotential of 285 mV than MoSe2 (367 mV) to reach a current density of 10 mA cm −2 in 1 M KOH. The improved catalytic activity is predominantly owing to the enhanced water dissociation kinetics of the heterostructures with well-defined interfaces. Density functional theory (DFT) calculations reveal that the presence of SnS2 significantly promotes the water adsorption capability of MoSe2 nanosheets, which consequently facilitates the subsequent water dissociation process. These results open up a new avenue for the rational design of well-defined heterostructures with enhanced water adsorption/dissociation capability for the development of high-performance alkaline HER electrocatalysts. Graphical abstract: Molybdenum dichalcogenide heterostructures with the SnS2 quantum dots decorated on the basal plane were synthesized via a universal wet chemical process as efficient alkaline HER electrocatalysts. DFT calculations also verify that incorporating SnS2 actually promotes water adsorption capability of MoSe2 both on the basal plane and edge sites.Image 1 Highlights: Molybdenum dichalcogenide heterostructures with the SnS2 decorated on the basal plane were synthesized via a universal wet chemical process. The heterostructured catalysts show greatly promoted alkaline HER activities. The activity enhancement is originated from the water adsorption/dissociation process. The DFT calculations reveal that SnS2 greatly enhance the water adsorption capability of MoSe2 both on the edge sites and basal plane.